2016
DOI: 10.1364/josab.34.000027
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation from plasmon polariton excitation on silver diffraction gratings: comparisons of theory and experiment

Abstract: We present a comparison between experimental and theoretical results for the diffraction efficiencies of the secondharmonic light produced in the orders of silver diffraction gratings. The gratings considered are sinusoidal, have depths of a few nanometers, and can produce significant surface plasmon polariton excitation at fundamental and second-harmonic frequencies. The calculations are based on a general expression for the nonlinear polarization of the surface of a homogeneous and isotropic medium, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Generating a maximum average output power of 190 pW with a maximum SHG conversion efficiency of 1.06 × 10 −9 . Taking the metasurface thickness into account, the maximum second order nonlinearity is 1.0 pm V −1 (see Supporting Information), which is of the same order of magnitude with respect to state-of-the-art metasurfaces [11,24,39]. Polynomial best-fitting finds a linear slope in the dou- ble log scale of 2.35.…”
Section: Shg Characterizationmentioning
confidence: 78%
See 1 more Smart Citation
“…Generating a maximum average output power of 190 pW with a maximum SHG conversion efficiency of 1.06 × 10 −9 . Taking the metasurface thickness into account, the maximum second order nonlinearity is 1.0 pm V −1 (see Supporting Information), which is of the same order of magnitude with respect to state-of-the-art metasurfaces [11,24,39]. Polynomial best-fitting finds a linear slope in the dou- ble log scale of 2.35.…”
Section: Shg Characterizationmentioning
confidence: 78%
“…In 1985 Coutaz et al showed that, as the incidence angle is changed, SHG undergoes strong enhancement in metallic mono-dimensional gratings when the im-pinging beam is resonant with the nonlocal surface plasmon [10], what is today known as SLR. However, in the same structure the SHG is also enhanced when the SLR condition is fullfield at the second harmonic frequency [11]. Similarly, for two-dimensional (2D) nanoparticle arrays the SHG is enhanced for the SLR at the fundamental frequency [12,13] and at the second harmonic [14].…”
Section: Introductionmentioning
confidence: 96%
“…16 Other approaches to realize high-efficiency SHG employ the field amplification in the structure because of the slow light effect (high density of modes) at photonic band edges, 79 or the strong light confinement in photonic cavities, defective and disordered superlattices, and plasmonic systems. 1027 The incorporation of artificial materials with a negative refractive index has led to striking phenomena in photonic superlattices. The so-called metamaterials with simultaneous negative dielectric permittivity (ε B ) and magnetic permeability (μ B ) 2834 yield superlattices with a gap under oblique incident light, i.e., θ ≠ 0, known as the magnetic/electric bulklike plasmon-polariton (PP) gap.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric superlattices, in particular, can be designed to have reciprocal lattice vectors, G n , to compensate the phase mismatch Δ k = k 2ω – 2 k ω , where k ω and k 2ω are the wavevectors of the fundamental field (FF) and second-harmonic (SH) waves, respectively. This enhances the second-harmonic (SH) conversion efficiency in a mechanism known as the quasi-phase-matching condition. Other approaches to realize high-efficiency SHG employ the field amplification in the structure because of the slow light effect (high density of modes) at photonic band edges, or the strong light confinement in photonic cavities, defective and disordered superlattices, and plasmonic systems. The incorporation of artificial materials with a negative refractive index has led to striking phenomena in photonic superlattices. The so-called metamaterials with simultaneous negative dielectric permittivity (ε B ) and magnetic permeability (μ B ) yield superlattices with a gap under oblique incident light, i.e., θ ≠ 0, known as the magnetic/electric bulklike plasmon-polariton (PP) gap.…”
Section: Introductionmentioning
confidence: 99%